Coesite in eclogites of the Lanterman Range (Antarctica): Evidence from textural and Raman studies - Ghiribelli, B; Frezzotti, M; Palmeri, R. (European Journal of Mineralogy, 2002)
Quartz pseudomorphs after possible retrogression of coesite were recognized petrographically within garnets of mafic eclogites from the Lanterman Range (Antarctica). In one of the quartz pseudomorphs the presence of a pristine coesite is indicated by in situ Raman microprobe spectroscopy. The results of the Raman analyses show that the quartz inclusion in addition to the typical quartz vibrations has a weak band at 521 cm(-1), which corresponds to the most intense fundamental vibration in coesite. This finding represents a first piece of evidence for ultrahigh-pressure metamorphism in Antarctica which was part of the Gondwana supercontinent affected by the Cambro-Ordovician orogenic cycle. Quartz pseudomorphs after possible retrogression of coesite were recognized petrographically within garnets of mafic eclogites from the Lanterman Range (Antarctica). In one of the quartz pseudomorphs the presence of a pristine coesite is indicated by in situ Raman microprobe spectroscopy. The results of the Raman analyses show that the quartz inclusion in addition to the typical quartz vibrations has a weak band at 521 cm-1, which corresponds to the most intense fundamental vibration in coesite. This finding represents a first piece of evidence for ultrahigh-pressure metamorphism in Antarctica which was part of the Gondwana supercontinent affected by the Cambro-Ordovician orogenic cycle.